1978
DOI: 10.1111/j.1469-1809.1978.tb00914.x
|View full text |Cite
|
Sign up to set email alerts
|

A cytogenetic study of spontaneous abortions in Hawaii

Abstract: Cytogenetic results on 234 spontaneous abortions showed 109 (46.6%) to have a chromosome abnormality. The results were analysed separately for the four major ethnic groups of which the population was composed and no differences in the proportion or types of chromosome abnormalities seen. The results of this survey were found to be very similar to other major published surveys and it therefore appears, on present evidence, that neither geographic location nor racial group affects the frequency of chromosome abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0
4

Year Published

1980
1980
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 12 publications
4
65
0
4
Order By: Relevance
“…For women over the age of 40 in the United States, roughly half of all clinical pregnancies established through IVF are lost, failing to result in live births (SART CORS Clinic Summary Report, 2012). It has been reported that approximately 50-80 % of all first trimester pregnancy losses result from chromosomal abnormalities in the developing fetus [4][5][6][7]. These abnormalities are a concern for couples seeking IVF treatment to conceive a healthy viable pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…For women over the age of 40 in the United States, roughly half of all clinical pregnancies established through IVF are lost, failing to result in live births (SART CORS Clinic Summary Report, 2012). It has been reported that approximately 50-80 % of all first trimester pregnancy losses result from chromosomal abnormalities in the developing fetus [4][5][6][7]. These abnormalities are a concern for couples seeking IVF treatment to conceive a healthy viable pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…So much so that in the end, one evening in June 1979, a Saturday night, I sat home at my dining room table to tell that story. However, no need then for any handy reprint, since abortion studies alone, among them the work of Hassold et al, 2 were to serve as the groundwork of this early summer dream. It so happened that, at the end of that night, on Sunday, I was still sitting at that table, putting the final dot on an initial draft.…”
Section: Introductionmentioning
confidence: 99%
“…Of all clinically recognized pregnancies, 10% to 15% end in miscarriage. Aneuploidy is found in the majority of first trimester miscarriages; multiple cytogenetic studies have demonstrated aneuploidy rates ranging from 50% to 80% in various populations [1][2][3][4]. Autosomal trisomies are the most frequent karyotypic abnormalities; however, polyploidies, sex chromosome monosomies, and structural rearrangements account for a substantial number of miscarriages [2].…”
Section: Introductionmentioning
confidence: 99%